A BiOBr / CNT-based hydrogel composite photothermal-photocatalytic membrane distillation membrane and its preparation method and application
By constructing the BiOBr/CNT@Alg hydrogel layer on the surface of the membrane distillation membrane, self-heating and in-situ catalytic degradation of the membrane interface are achieved, the problems of temperature difference polarization and low retention of volatile organic compounds in membrane distillation are solved, and the energy utilization efficiency of membrane distillation and the purification effect of water are improved.
Patent Information
- Application Number
- CN202410934394.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-12
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2044-07-12
AI Technical Summary
The temperature difference polarization phenomenon in membrane distillation technology leads to reduced flux and energy loss, and the traditional membrane has low retention rate of volatile organic compounds, which affects the purification effect of water.
Using BiOBr/CNT-based hydrogel composite photothermal-photocatalytic film, the BiOBr/CNT@Alg hydrogel layer is constructed on the surface of the hydrophobic membrane to achieve self-heating at the membrane interface and in-situ catalytic degradation, thereby improving the retention and degradation efficiency of volatile organic compounds.
Effectively alleviate the phenomenon of temperature difference polarization, improve the energy utilization efficiency of membrane distillation, and achieve efficient retention and degradation of volatile organic compounds, and improve the purification effect of water.
Smart Images

Figure CN118807498B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of membrane distillation, and in particular relates to a BiOBr / CNT-based hydrogel composite photothermal-photocatalytic membrane distillation membrane and a preparation method and application thereof. Background Art
[0002] Membrane distillation (MD) is an emerging membrane separation process based on heat-driven separation. It uses a hydrophobic microporous membrane as the separation medium and the temperature difference of the solution on both sides of the membrane as the driving force. It allows volatile components (such as water vapor) to pass through the membrane pores and then cool into fresh water on the permeate side, while intercepting non-volatile components (such as salt) from passing through the membrane pores to achieve the desalination process. Compared with desalination technologies such as reverse osmosis and conventional distillation processes, membrane distillation shows significant advantages, such as insensitivity to feed solution salt concentration, high salt rejection rate, simple equipment, and modularity. However, the temperature polarization phenomenon is one of the main challenges currently faced by membrane distillation technology. It refers to the temperature at the membrane interface on the feed liquid side being lower than the feed liquid body temperature, resulting in a decrease in the actual effective temperature difference across the membrane, thereby reducing the flux and increasing the energy loss in the membrane distillation process. In addition, although membrane distillation technology can achieve nearly 100% retention of non-volatile substances, due to the high Henry constant and molecular kinetic size of volatile organic compounds (VOCs) similar to that of water molecules, the retention rate of VOCs by traditional MD hydrophobic microporous membranes is very low. Small molecule VOCs can evaporate with water vapor through the membrane pores and condense, collect and enrich on the permeate side, making the produced water unable to meet the discharge or reuse standards, hindering its application in polluted water treatment scenarios.
[0003] Photothermal membrane distillation (PMD) technology usually integrates photothermal materials into MD membranes, uses solar energy to achieve photothermal conversion effects and locally heats the membrane surface, thereby alleviating temperature polarization and improving energy utilization efficiency. Among them, carbon-based photothermal nanomaterials (such as carbon nanotubes (CNTs)) have the advantages of relatively low cost and wide spectrum light absorption ability and are widely used in the preparation of PMD membranes, but there are few studies on the design and development of functionalized PMD membranes for VOCs removal. In order to achieve the interception of VOCs in the PMD process, functional materials with synergistic photothermal conversion and photocatalytic activity are organically combined with the surface of the hydrophobic membrane to construct a photothermal-photocatalytic functional layer with interfacial self-heating and in-situ catalytic degradation performance, which is expected to achieve efficient and sustainable water purification in the PMD process. Bismuth oxybromide (BiOBr) is a newly discovered semiconductor photocatalytic material with a narrow bandgap and responsiveness in the visible light region. However, there is currently no relevant research on BiOBr composite PMD membranes for photocatalytic degradation of VOCs.
[0004] Therefore, how to develop a BiOBr-based photothermal-photocatalytic MD membrane with high VOCs removal rate, anti-pollution, and durability to ensure its sustainable and stable operation in the process of high-salt wastewater treatment and seawater desalination is a technical problem that technical personnel in this field urgently need to solve. Summary of the invention
[0005] In order to solve the above technical problems, the present invention proposes a BiOBr / CNT-based hydrogel composite photothermal-photocatalytic membrane distillation membrane and a preparation method and application thereof.
[0006] To achieve the above object, the present invention provides the following technical solutions:
[0007] A method for preparing a BiOBr / CNT-based hydrogel composite photothermal-photocatalytic membrane distillation membrane comprises the following steps:
[0008] The BiOBr / CNT@Alg hydrogel precursor solution and the alginate (Alg) hydrogel precursor solution are uniformly coated on a hydrophilically modified hydrophobic membrane surface in sequence, and then infiltrated and cross-linked using an ion cross-linking liquid to obtain an Alg-BiOBr / CNT hydrogel composite photothermal-photocatalytic membrane distillation membrane.
[0009] Preferably, the uniform coating in sequence specifically comprises:
[0010] The BiOBr / CNT@Alg hydrogel precursor solution is uniformly coated on a hydrophilically modified hydrophobic membrane surface, and after drying, a BiOBr / CNT@Alg pregel layer is formed to obtain a BiOBr / CNT@Alg pregel composite membrane;
[0011] The alginate hydrogel precursor solution is uniformly coated on the BiOBr / CNT@Alg pregel composite film, and after drying, an Alg-BiOBr / CNT composite pregel layer is formed to obtain an Alg-BiOBr / CNT pregel composite film.
[0012] Beneficial effects: The present invention uses a hydrophilically modified hydrophobic microporous membrane, which is beneficial to the loading of the BiOBr / CNT@Alg coating, thereby ensuring the formation of a uniform and defect-free pre-gel coating on the surface of the hydrophobic membrane. The BiOBr used in the present invention is a newly discovered semiconductor photocatalytic material with a narrow bandgap and responsive to the visible light region. In addition, BiOBr has a unique nano-layered structure, which is beneficial to the separation and transfer of photogenerated electrons and holes. When combined with CNT, it can further reduce the electron / hole recombination rate, thereby improving its photocatalytic activity. The present invention uses Alg natural polysaccharide compounds as the matrix of the hydrogel coating, which has good water solubility and biodegradability, and contains rich hydroxyl and carboxyl hydrophilic groups on the surface. Dispersing CNT and BiOBr in the Alg solution can not only improve the dispersibility and stability of CNT and BiOBr micro-nano materials, but also enhance the strength of the hydrogel coating.
[0013] The present invention combines CNT with photothermal conversion characteristics with BiOBr materials with photocatalytic activity to achieve a water purification process with high efficiency of membrane interface self-heating and in-situ catalytic degradation. Further, a dense polymer molecular chain network is formed through hydrogen bonding and ionic crosslinking between Alg molecular chains. Since the dense Alg hydrogel network layer itself allows free diffusion and penetration of water molecules, it effectively inhibits the penetration and diffusion of pollutants. A small amount of pollutants that are not intercepted by the dense Alg hydrogel layer can be further degraded in situ by the BiOBr / CNT@Alg composite layer, thereby realizing efficient removal of volatile organic compounds in the PMD process by intercepting-degrading double-layer protective layers. In addition, due to the hydrophilicity of the hydrogel layer in the air and the underwater superoleophobic properties, a firm hydration layer is formed in water, which can effectively prevent the adhesion and pollution of oil substances.
[0014] Preferably, the thickness of the BiOBr / CNT@Alg pre-gel layer is 1-5 μm;
[0015] The Alg-BiOBr / CNT composite pre-gel layer has a thickness of 2-10 μm.
[0016] Preferably, the drying is air-drying or drying at 25-35°C.
[0017] Preferably, the uniform coating is performed using a scraper with a gap of 50 microns.
[0018] Preferably, the BiOBr is a BiOBr micro-nano material having photocatalytic activity;
[0019] The CNT is a CNT nanomaterial with light-to-heat conversion properties.
[0020] Preferably, the method for preparing the BiOBr / CNT@Alg hydrogel precursor solution comprises the following steps:
[0021] BiOBr and CNT were added to deionized water and ultrasonically treated to obtain a BiOBr / CNT suspension, and then Alg powder was added under rapid stirring to obtain a BiOBr / CNT@Alg hydrogel precursor solution.
[0022] Preferably, the ultrasonic time is 25 min; the rapid stirring speed is 500-1000 rpm.
[0023] Preferably, in the BiOBr / CNT@Alg hydrogel precursor solution, the mass concentration of alginate is 1-4%, the concentration of CNT is 5-25 mg / mL, and the concentration ratio of CNT to BiOBr is (0.2-2):1.
[0024] Preferably, in the alginate hydrogel precursor solution, the mass concentration of alginate is 3-8%.
[0025] Beneficial effects: Alg in the present invention is a biomass material extracted from algae, which has the advantages of wide sources, low price, and biodegradability. Alg contains abundant carboxyl (-COOH) and hydroxyl (-OH) groups and is easy to ion cross-link, so it is widely used in the preparation of hydrogels.
[0026] Preferably, the hydrophobic membrane comprises one of polytetrafluoroethylene, polyvinylidene fluoride, polypropylene and composite materials thereof.
[0027] Preferably, the hydrophilic modification comprises one or any combination of polydopamine deposition, polydopamine / polyethyleneimine deposition, tannic acid / 3-aminopropyltriethoxysilane adhesion, sodium hydroxide solution immersion, and plasma treatment.
[0028] Preferably, the ionic cross-linking liquid is an aqueous solution of a multivalent metal salt, wherein the metal ion concentration is 0.1-1 mol / L.
[0029] Preferably, the multivalent metal salt is one or any combination of aluminum chloride, aluminum sulfate, ferric chloride and ferric sulfate.
[0030] Preferably, the time of the infiltration and cross-linking is 0.5-24h.
[0031] A BiOBr / CNT-based hydrogel composite photothermal-photocatalytic membrane distillation membrane is prepared by a method for preparing a BiOBr / CNT-based hydrogel composite photothermal-photocatalytic membrane distillation membrane.
[0032] Application of a BiOBr / CNT-based hydrogel composite photothermal-photocatalytic membrane distillation membrane in photothermal membrane distillation.
[0033] Preferably, in the application, the side of the Alg-BiOBr / CNT hydrogel composite photothermal-photocatalytic membrane distillation membrane loaded with the Alg-BiOBr / CNT composite hydrogel layer is contacted with the feed liquid, and the light intensity is 1KW m -2 .
[0034] The two sides of the membrane distillation membrane are respectively a feed liquid on the hot side and a permeate on the cold side. The feed liquid is a salt solution, more preferably a salt solution with volatile organic matter, a surfactant and an oil-water emulsion stabilized by a surfactant, and the permeate is deionized water.
[0035] Beneficial effects: The present invention adds volatile organic compounds to the feed liquid in order to test the performance of the BiOBr / CNT-based hydrogel composite photothermal-photocatalytic membrane distillation membrane in intercepting and catalytically degrading volatile organic compounds; adds surfactants to the feed liquid in order to test the anti-wetting performance of the BiOBr / CNT-based hydrogel composite photothermal-photocatalytic membrane distillation membrane; adds surfactant-stabilized oil-water emulsions to the feed liquid in order to test the simultaneous anti-pollution and anti-wetting performance of the BiOBr / CNT-based hydrogel composite photothermal-photocatalytic membrane distillation membrane.
[0036] Compared with the prior art, the present invention has the following advantages and technical effects:
[0037] First, the present invention utilizes the strategy of "pre-gel construction combined with ionic cross-linking reinforcement" to integrate photothermal and photocatalytic materials on the surface of the polymer membrane, realize interfacial heating of the membrane surface and in-situ photocatalytic degradation, thereby simultaneously alleviating the temperature polarization phenomenon and degrading and removing volatile organic compounds, and further loading a hyper-cross-linked and dense hydrogel layer on its surface to achieve selective permeation of water and volatile organic compounds. A small amount of volatile organic compounds that permeate through the Alg hydrogel layer will be further removed by in-situ catalytic degradation by the photothermal-photocatalytic functional layer. Secondly, the surface of the BiOBr / CNT-based hydrogel composite photothermal-photocatalytic membrane distillation membrane prepared by the present invention has a dense hydrogel structure and strong hydration, which can effectively intercept surfactants and prevent the adhesion of oil substances, thereby preventing them from directly contacting the hydrophobic membrane and thus preventing membrane wetting and membrane pollution. The BiOBr / CNT-based hydrogel composite photothermal-photocatalytic membrane distillation membrane prepared by the present invention exhibits excellent long-term pollution resistance, anti-wetting and high-efficiency interception-catalytic degradation of volatile organic compounds when treating saline wastewater containing surfactants, surfactant-stabilized oil-water emulsions and volatile organic compounds. In addition, the hydrogel material used in the present invention is a green, environmentally friendly and low-cost natural polysaccharide compound, and the BiOBr / CNT-based hydrogel composite photothermal-photocatalytic membrane distillation membrane is prepared by a simple and easy-to-operate pre-gel coating-ion crosslinking strategy. Compared with other membrane distillation membrane preparation methods, it is more economical and environmentally friendly, and is conducive to industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] The drawings constituting a part of the present application are used to provide a further understanding of the present application. The illustrative embodiments and descriptions of the present application are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings:
[0039] Figure 1 This is a surface electron microscope image of the polytetrafluoroethylene hydrophobic microporous membrane of Example 1;
[0040] Figure 2 This is the surface electron microscopy image of the Alg-BiOBr / CNT film of Example 1;
[0041] Figure 3 The flux diagram of the polytetrafluoroethylene film and the Alg-BiOBr / CNT film of Example 1 in the absence of light and under 1 sun;
[0042] Figure 4 The graph of the surface temperature of the polytetrafluoroethylene film and the Alg-BiOBr / CNT film of Example 2 changing with time under the irradiation of one sun;
[0043] Figure 5 The contact angles of water in air and oil in water of the polytetrafluoroethylene film and the Alg-BiOBr / CNT film of Example 2 are shown;
[0044] Figure 6 The graphs are the flux and effluent conductivity of the polyvinylidene fluoride membrane and the Alg-BiOBr / CNT membrane of Example 3 when treating a salt solution of an oil-water emulsion stabilized by a surfactant as the feed liquid;
[0045] Figure 7 is a graph showing the rejection rate of aniline by the polytetrafluoroethylene membrane and the Alg-BiOBr / CNT membrane of Example 4;
[0046] Figure 8 This is a graph showing the retention rate of phenol by the polytetrafluoroethylene membrane and the Alg-BiOBr / CNT membrane of Example 4. DETAILED DESCRIPTION
[0047] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0048] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the present invention is further described in detail below with reference to the accompanying drawings and specific embodiments.
[0049] Except for the BiOBr material prepared by the solvothermal method, the other raw materials in the present invention are purchased from commercial sources.
[0050] Unless otherwise specified, the operating temperature in the embodiments of the present invention is room temperature.
[0051] Example 1
[0052] A method for preparing a BiOBr / CNT-based hydrogel composite photothermal-photocatalytic membrane distillation membrane comprises the following steps:
[0053] 1) 0.2 g dopamine and 0.2 g polyethyleneimine were dissolved in 100 ml of 50 mmol / L Tris-HCl buffer solution (pH=8) to obtain an activation solution, and then the upper surface of a polytetrafluoroethylene membrane (polytetrafluoroethylene hydrophobic microporous membrane) was immersed in the activation solution, and after standing for 10 hours, the membrane surface was rinsed and naturally dried to obtain a polytetrafluoroethylene membrane with one side hydrophilically modified;
[0054] 2) 0.1 g BiOBr and 0.1 g CNT were added to 10 ml deionized water, and a BiOBr / CNT suspension was obtained after ultrasonic treatment for 25 min. 0.2 g Alg powder was added to the BiOBr / CNT suspension under rapid stirring at a stirring rate of 1000 rpm to obtain a BiOBr / CNT@Alg hydrogel precursor solution, which was cast on the surface of the hydrophilically modified polytetrafluoroethylene membrane prepared in step 1), and evenly coated using a scraper with a gap of 50 μm. After evenly coating, the solution was dried at room temperature for 1 hour to obtain a BiOBr / CNT@Alg pregel composite membrane, wherein the thickness of the BiOBr / CNT@Alg pregel layer was about 2 μm;
[0055] 3) Under rapid stirring at a stirring rate of 1000 rpm, 0.3 g of Alg was added to 9.7 g of ionized water to obtain an Alg hydrogel precursor solution with a mass fraction of 3%, and the solution was poured onto the surface of the BiOBr / CNT@Alg pregel composite film obtained in step 2), and the solution was evenly coated using a scraper with a gap of 50 μm. After the coating was evenly applied, the solution was dried at room temperature for 1 hour to obtain an Alg-BiOBr / CNT pregel composite film, wherein the thickness of the Alg-BiOBr / CNT composite pregel layer was 5 μm;
[0056] 4) The Alg-BiOBr / CNT pregel composite membrane obtained in step 3) is immersed in a 0.5 mol / L AlCl3 ion solution for ionic crosslinking for 12 hours, and then the excess ionic liquid is poured off and the membrane surface is thoroughly rinsed with deionized water to obtain an Alg-BiOBr / CNT hydrogel composite photothermal-photocatalytic membrane distillation membrane (BiOBr / CNT-based hydrogel composite photothermal-photocatalytic membrane distillation membrane, or Alg-BiOBr / CNT membrane).
[0057] Technical effect:
[0058] The surfaces of the polytetrafluoroethylene microporous membrane used in Example 1 and the obtained hydrogel composite photothermal-photocatalytic membrane distillation membrane were characterized by scanning electron microscopy.
[0059] Figure 1 This is the surface electron microscope image of the original polytetrafluoroethylene membrane (polytetrafluoroethylene hydrophobic microporous membrane). Figure 2 This is the surface electron microscopy image of the obtained Alg-BiOBr / CNT film.
[0060] Depend on Figure 1-2 It can be seen that the surface of the polytetrafluoroethylene hydrophobic microporous membrane exhibits a porous morphology of mesh fiber nodules. In contrast, the surface of the obtained Alg-BiOBr / CNT hydrogel composite photothermal-photocatalytic membrane distillation membrane is relatively dense and non-porous, showing some protrusions, which are mainly attributed to CNT aggregates and BiOBr micro-nanoparticles.
[0061] Application Effect
[0062] The performance of the membrane was tested by a direct contact photothermal membrane distillation device. A solution containing 3.5 wt% sodium chloride was used as the feed liquid. The hydrogel layer faced the feed liquid. The feed side temperature was set to 30 °C, the permeate side temperature was set to 20 °C, and the light intensity on the membrane surface was 1 kW m -2 The photothermal desalination performance of the Alg-BiOBr / CNT hydrogel composite photothermal-photocatalytic membrane distillation membrane obtained in Example 1 was tested. The results are as follows Figure 3 shown.
[0063] Depend on Figure 3 It can be seen that when no light is added, the calculated permeation fluxes of the polytetrafluoroethylene membrane and the Alg-BiOBr / CNT hydrogel composite photothermal-photocatalytic membrane distillation membrane are 2.42 kg m -2 h -1 and 2.44 kg m -2 h -1 When one sun is added, the permeation flux of polytetrafluoroethylene membrane and Alg-BiOBr / CNT hydrogel composite photothermal-photocatalytic membrane distillation membrane are 2.38 kg m -2 h -1 and 2.92 kg m -2 h -1 This indicates that the Alg-BiOBr / CNT hydrogel composite photothermal-photocatalytic membrane distillation membrane has excellent photothermal conversion properties, which promotes a larger transmembrane temperature difference by increasing the membrane surface temperature, thereby achieving a high freshwater yield.
[0064] Example 2
[0065] A method for preparing a BiOBr / CNT-based hydrogel composite photothermal-photocatalytic membrane distillation membrane, which is different from Example 1 only in that the anhydrous aluminum chloride (AlCl3) in step 4) is replaced by an equal amount and concentration of anhydrous ferric chloride (FeCl3), and the other process steps and parameters are the same as Example 1.
[0066] Technical effect:
[0067] 1) The photothermal conversion properties of the Alg-BiOBr / CNT hydrogel composite photothermal-photocatalytic membrane distillation membrane obtained in Example 2 were tested. The results are as follows: Figure 4 shown.
[0068] Figure 4 The surface temperature of polytetrafluoroethylene membrane and hydrogel composite photothermal-photocatalytic membrane distillation membrane varies with time under 1 sun intensity. Figure 4It can be seen that under the irradiation of 1 sun, the surface equilibrium temperature of the Alg-BiOBr / CNT hydrogel composite photothermal-photocatalytic membrane distillation membrane reaches 86.3°C, while the surface equilibrium temperature of the polytetrafluoroethylene membrane reaches 35.0°C, indicating that the Alg-BiOBr / CNT hydrogel composite photothermal-photocatalytic membrane distillation membrane has excellent photothermal conversion properties.
[0069] 2) The surface wetting properties of the Alg-BiOBr / CNT hydrogel composite photothermal-photocatalytic membrane distillation membrane obtained in Example 2 were tested. The results are as follows: Figure 5 shown.
[0070] Figure 5 The contact angle of water in air and oil in water of the composite photothermal-photocatalytic membrane distillation membrane of polytetrafluoroethylene membrane and hydrogel is shown in Fig. Figure 5 It can be seen that the polytetrafluoroethylene membrane has strong hydrophobicity, with a water contact angle of 154.3° in the air, and is oleophilic underwater, with an underwater oil contact angle of only 16.1°, which is mainly attributed to the strong hydrophobic-hydrophobic interaction between the oil droplets and the polytetrafluoroethylene membrane surface. In contrast, the surface of the Alg-BiOBr / CNT hydrogel composite photothermal-photocatalytic membrane distillation membrane is hydrophilic in the air (the water contact angle in the air is 58.0°), and exhibits superoleophobic properties underwater (the underwater oil contact angle is 153.1°), which is mainly attributed to the hydration layer formed on the surface of the Alg-BiOBr / CNT hydrogel composite photothermal-photocatalytic membrane distillation membrane, which can inhibit the attachment of oil droplets, indicating that the Alg-BiOBr / CNT hydrogel composite photothermal-photocatalytic membrane distillation membrane has excellent anti-fouling potential.
[0071] Example 3
[0072] A method for preparing a BiOBr / CNT-based hydrogel composite photothermal-photocatalytic membrane distillation membrane comprises the following steps:
[0073] 1) dissolving 0.2 g dopamine and 0.2 g 3-aminopropyltriethoxysilane in 100 ml of 50 mmol / L Tris-HCl buffer solution (pH=8) to obtain an activation solution, then soaking the upper surface of the polyvinylidene fluoride membrane in the activation solution, standing for 6 hours, then rinsing the membrane surface and drying it naturally to obtain a polyvinylidene fluoride membrane with one side hydrophilically modified;
[0074] 2) 0.2 g BiOBr and 0.1 g CNT were added to 10 ml deionized water, and a BiOBr / CNT suspension was obtained after ultrasonic treatment for 25 min. 0.3 g Alg powder was added to the BiOBr / CNT suspension under rapid stirring at a stirring rate of 800 rpm to obtain a BiOBr / CNT@Alg hydrogel precursor solution, which was cast on the surface of the hydrophilically modified polyvinylidene fluoride membrane obtained in step 1), and was evenly coated using a scraper with a gap of 50 μm. After uniform coating, the solution was placed at room temperature and dried for 1 hour to obtain a BiOBr / CNT@Alg pregel composite membrane, wherein the thickness of the BiOBr / CNT@Alg pregel layer was about 2 μm;
[0075] 3) under rapid stirring at a stirring rate of 1000 rpm, 0.4 g of Alg was added to 9.6 g of ionized water to obtain an Alg hydrogel precursor solution with a mass fraction of 4%, and the solution was poured onto the surface of the BiOBr / CNT@Alg pregel composite film obtained in step 2), and the solution was evenly coated using a scraper with a gap of 100 μm. After the coating was evenly applied, the solution was dried at room temperature for 1 hour to obtain an Alg-BiOBr / CNT pregel composite film, wherein the thickness of the Alg-BiOBr / CNT composite pregel layer was about 6 μm;
[0076] 4) The Alg-BiOBr / CNT pregel composite membrane obtained in step 3) is immersed in a 0.5 mol / L AlCl3 ion solution for ionic crosslinking for 24 hours, and then the excess ionic liquid is poured off and the membrane surface is thoroughly rinsed with deionized water to obtain an Alg-BiOBr / CNT hydrogel composite photothermal-photocatalytic membrane distillation membrane (BiOBr / CNT-based hydrogel composite photothermal-photocatalytic membrane distillation membrane, or Alg-BiOBr / CNT membrane).
[0077] Application Effect
[0078] The performance of the membrane was tested by a direct contact photothermal membrane distillation device. A solution containing 3.5 wt% sodium chloride, 1000 ppm mineral oil and 0.1 mM sodium dodecyl sulfate was used as the feed liquid. The hydrogel composite layer faced the feed liquid. The feed side temperature was set to 30 °C, the condensation side temperature was set to 20 °C, and the light intensity on the membrane surface was set to 1 kW m -2 The anti-fouling and anti-wetting properties of the Alg-BiOBr / CNT hydrogel composite photothermal-photocatalytic membrane distillation membrane obtained in Example 3 were tested. The results are as follows Figure 6 As shown. Figure 6It can be seen that the flux of the polyvinylidene fluoride membrane increased sharply within 6 hours, and the effluent conductivity surged to 6839μS / cm, while the Alg-BiOBr / CNT hydrogel composite photothermal-photocatalytic membrane distillation membrane still had a stable flux and very low effluent conductivity (3.18μS / cm) after running for 120 hours. This result data shows that the Alg-BiOBr / CNT hydrogel composite photothermal-photocatalytic membrane distillation membrane has both excellent pollution resistance and anti-wetting properties, mainly due to the dense structure and strong hydration of the hydrogel composite layer, thereby preventing the hydrophobic base membrane from contacting with pollutants. This result shows that the Alg-BiOBr / CNT hydrogel composite photothermal-photocatalytic membrane distillation membrane can still achieve efficient solar membrane distillation performance when treating contaminated high-salt solutions.
[0079] Example 4
[0080] A method for preparing a BiOBr / CNT-based hydrogel composite photothermal-photocatalytic membrane distillation membrane, which is different from Example 1 only in that:
[0081] In step 1), the polyvinylidene fluoride membrane is replaced with a polytetrafluoroethylene membrane, and after standing for 12 hours, the membrane surface is rinsed and naturally dried to obtain a polytetrafluoroethylene membrane with one side being hydrophilically modified;
[0082] In step 4), anhydrous aluminum chloride (AlCl3) is replaced with an equal amount of iron sulfate (Fe2(SO4)3) of equal concentration.
[0083] The other process steps and parameters are the same as those in Example 1.
[0084] Application Effect
[0085] The performance of the membrane was tested by a direct contact photothermal membrane distillation device. A solution containing 3.5 wt% sodium chloride, different concentrations of aniline or phenol was used as the feed liquid. The hydrogel composite layer faced the feed liquid. The feed side temperature was set to 30 °C, the condensation side temperature was set to 20 °C, and the light intensity on the membrane surface was set to 1 KW m -2 , and when a certain amount of permeate is accumulated, the concentration of aniline or phenol in the permeate solution is detected, and the interception rate of volatile organic compounds of the Alg-BiOBr / CNT hydrogel composite photothermal-photocatalytic membrane distillation membrane prepared in Example 4 is tested. The results are as follows Figure 7 and 8 shown.
[0086] Figure 7 The figure is a graph showing the retention rate of aniline of different concentrations by the polytetrafluoroethylene membrane and the Alg-BiOBr / CNT hydrogel composite photothermal-photocatalytic membrane distillation membrane of Example 4. Figure 8The figure is a graph showing the retention rate of phenol at different concentrations by the polytetrafluoroethylene membrane and the Alg-BiOBr / CNT hydrogel composite photothermal-photocatalytic membrane distillation membrane of Example 4. Figure 7 and Figure 8 It can be seen that when the polytetrafluoroethylene membrane and the prepared Alg-BiOBr / CNT hydrogel composite photothermal-photocatalytic membrane distillation membrane treat salt solutions containing volatile organic compounds, the polytetrafluoroethylene membrane has a retention rate of 0 for aniline and phenol with a concentration greater than 10 ppm. In contrast, the Alg-BiOBr / CNT hydrogel composite photothermal-photocatalytic membrane distillation membrane has a very high retention rate for aniline and phenol, with the retention rates for 10 ppm aniline and 100% for 10 ppm phenol being 95.19% and 100%, respectively, indicating that the Alg-BiOBr / CNT hydrogel composite photothermal-photocatalytic membrane distillation membrane has the performance of efficiently retaining volatile organic compounds.
[0087] Comparative Example 1
[0088] A method for preparing a degradable polyvinyl alcohol / chitosan / cyanobacteria composite film is prepared according to the technical scheme in Example 1 of application number 202311730979.3.
[0089] Compared with Comparative Example 1, the Alg-BiOBr / CNT pregel composite membrane obtained in Example 1 is immersed in AlCl3 ion cross-linking liquid to form a BiOBr / CNT-based hydrogel composite photothermal-photocatalytic membrane distillation membrane under room temperature conditions. The ion cross-linking liquid used is more green and economical, and the operating conditions are milder.
[0090] Comparative Example 2
[0091] A method for preparing an Alg / M hydrogel composite film specifically comprises the following steps:
[0092] 1) 0.2 g dopamine and 0.2 g polyethyleneimine were dissolved in 100 ml of 50 mmol / L Tris-HCl buffer solution (pH=8) to obtain an activation solution, and then the upper surface of a polytetrafluoroethylene membrane (polytetrafluoroethylene hydrophobic microporous membrane) was immersed in the activation solution, and after standing for 10 hours, the membrane surface was rinsed and naturally dried to obtain a polytetrafluoroethylene membrane with one side hydrophilically modified;
[0093] 2) under rapid stirring at a stirring rate of 1000 rpm, 0.3 g of Alg was added to 9.7 g of ionized water to obtain an Alg hydrogel precursor solution with a mass fraction of 3%, and the solution was cast on the surface of the polytetrafluoroethylene membrane with one side hydrophilically modified obtained in step 1), and the solution was evenly coated using a scraper with a gap of 50 μm. After the coating was evenly applied, the solution was dried at room temperature for 1 hour to obtain an Alg pregel film, wherein the thickness of the Alg pregel layer was 5 μm;
[0094] 3) The Alg pregel membrane obtained in step 3) is immersed in a 0.5 mol / L AlCl3 ion solution for ionic crosslinking for 12 h, and then the excess ionic liquid is poured off and the membrane surface is thoroughly rinsed with deionized water to obtain an Alg / M hydrogel composite membrane.
[0095] Compared with Comparative Example 2, the Alg-BiOBr / CNT hydrogel layer formed on the surface of the hydrophobic membrane in Example 1 has both photothermal conversion characteristics and photocatalytic activity, and can achieve the performance of self-heating of the composite membrane interface and in-situ catalytic degradation, thereby effectively alleviating the energy loss problem caused by the temperature polarization phenomenon and achieving efficient interception and degradation of volatile organic compounds. Comparative Example 2 does not have the above technical effects.
[0096] The above are only preferred specific implementations of the present application, but the protection scope of the present application is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed in the present application should be included in the protection scope of the present application. Therefore, the protection scope of the present application should be based on the protection scope of the claims.
Claims
1. A method for preparing a BiOBr / CNT-based hydrogel composite photothermal-photocatalytic membrane distillation membrane, characterized in that: The following steps are involved: The BiOBr / CNT@Alg hydrogel precursor solution and the alginate hydrogel precursor solution are sequentially and evenly coated on the surface of a hydrophilically modified hydrophobic membrane, and then infiltrated and cross-linked with an ion cross-linking liquid to obtain an Alg-BiOBr / CNT hydrogel composite photothermal-photocatalytic membrane distillation membrane; The preparation method of the BiOBr / CNT@Alg hydrogel precursor solution comprises the following steps: BiOBr and CNT were added to deionized water and ultrasonically treated to obtain a BiOBr / CNT suspension, and then Alg powder was added under rapid stirring to obtain a BiOBr / CNT@Alg hydrogel precursor solution; In the BiOBr / CNT@Alg hydrogel precursor solution, the mass concentration of alginate is 1-4%, the concentration of CNT is 5-25 mg / mL, and the concentration ratio of CNT to BiOBr is (0.2-2):
1.
2. The method for preparing a BiOBr / CNT-based hydrogel composite photothermal-photocatalytic membrane distillation membrane according to claim 1, characterized in that: In the alginate hydrogel precursor solution, the mass concentration of alginate is 3-8%.
3. The method for preparing a BiOBr / CNT-based hydrogel composite photothermal-photocatalytic membrane distillation membrane according to claim 1, characterized in that: The hydrophobic membrane comprises one of polytetrafluoroethylene, polyvinylidene fluoride, polypropylene and composite materials thereof.
4. The method for preparing a BiOBr / CNT-based hydrogel composite photothermal-photocatalytic membrane distillation membrane according to claim 1, characterized in that: The hydrophilic modification includes one or any combination of polydopamine deposition, polydopamine / polyethyleneimine deposition, tannic acid / 3-aminopropyltriethoxysilane adhesion, sodium hydroxide solution immersion, and plasma treatment.
5. The method for preparing a BiOBr / CNT-based hydrogel composite photothermal-photocatalytic membrane distillation membrane according to claim 1, characterized in that: The ionic cross-linking liquid is an aqueous solution of a multivalent metal salt, wherein the concentration of the metal ions is 0.1-1 mol / L.
6. The method for preparing a BiOBr / CNT-based hydrogel composite photothermal-photocatalytic membrane distillation membrane according to claim 5, characterized in that: The multivalent metal salt is one or any combination of aluminum chloride, aluminum sulfate, ferric chloride and ferric sulfate.
7. The method for preparing a BiOBr / CNT-based hydrogel composite photothermal-photocatalytic membrane distillation membrane according to claim 1, characterized in that: The time of the infiltration and cross-linking is 0.5-24h.
8. A BiOBr / CNT-based hydrogel composite photothermal-photocatalytic membrane distillation membrane prepared by the method for preparing a BiOBr / CNT-based hydrogel composite photothermal-photocatalytic membrane distillation membrane as described in any one of claims 1 to 7.
9. Use of a BiOBr / CNT-based hydrogel composite photothermal-photocatalytic membrane distillation membrane as claimed in claim 8 in photothermal membrane distillation.
Citation Information
Patent Citations
Preparation method of degradable polyvinyl alcohol / chitosan / blue-green algae composite membrane
CN117700787A
Catalyst and preparation method and application thereof
CN112007669A
Alg / M hydrogel composite membrane as well as preparation method and application thereof
CN116832625A